The Effects of Social Media Use Intensity on Student's Religious Knowledge in Yogyakarta - Latif, Khusna Haibati; Kistoro, Hanif Cahyo; Muhliana, Syafira Intan; Sari, Prima Rosita (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
Progress technology gives convenience in many ways, one of which is communication and information. The form of progress technology, can be seen in the presence of social media. Social media presents various modern and instant features, making it easier for users to access multiple pieces of information related to religious knowledge. The purpose of this study is to find out how much influence the intensity of using social media has on the spiritual understanding of students in Yogyakarta. The research method used is the quantitative method with type study correlational respondent in a study this totaling 150 students. As for the step withdrawal sample, the researcher takes 25% of the whole population with simple random sampling. The variable independent in a study is the intensity of use of social media (X), whereas the variable dependent is the enhancement of religious knowledge (Y). The researcher use the data collection technique in the form of a questionnaire, then to find out the study results using the help of the statistical software application SPSS version 23. The research results show that, the level of intensity used by social media students enters in the category currently with a percentage of 68%, and increased knowledge religion classified in the class currently with a rate of 73% based on results analysis descriptive frequency. Whereas based on results analysis regression, there is a significant effect (r) Among intensity use of social media to enhance knowledge of religious FAI students class of 2018 amounted to 65.9 with a significance as considerable as 0.000 < 0.05. While R square is 43.5, contribution variable x is by 43.5 percent. The results above analysis could conclude that the more tall use of social media for religious content, the more and more knowledgeable religious students. The results of this research can be a simple reference for further research development. Religious knowledge can be obtained from social media, especially religious content that is made simple and more meaningful.